Strategi Meningkatkan Keterampilan Menulis Siswa melalui Metode Peer Feedback di MI Mabdaul Huda Kedungkarang Wedung Demak Jawa Tengah - Kafa, Nurul; Ropikoh, Siti; Hidayah, Nurul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Writing skills are a basic ability that must be mastered by elementary school students because it plays an important role in the development of their thinking and expression. However, observations at MI Mabdaul Huda Kedungkarang Wedung Demak show that students' writing skills are still low due to lack of motivation, lack of practice, and conventional learning methods. This study aims to examine the effectiveness of the peer feedback method in improving students' writing skills. This study used classroom action research (PTK) method conducted in two cycles, involving planning, implementation, observation, and reflection. Data were collected through observation, interviews, as well as analysis of students' writing before and after the application of the peer feedback method. The results showed that this method significantly improved students' writing skills, both in writing structure, grammar, and coherence of ideas. In addition, this method increases students' motivation, critical thinking skills, and sense of responsibility in learning. With the results obtained, the peer feedback method is recommended to be applied in learning writing in elementary schools. It is expected that teachers can develop this technique to be more effective, and schools can provide training to support its optimal implementation